Comparação entre os efeitos da exposição em nível subletal de glifosato e dos herbicidas a base de glifosato Roundup Original® e Roundup Transorb R® sobre girinos de rã-touro - Rissoli, Rafael Zanelli (2012)
Glyphosate based herbicides are widely used in agriculture and fishery to control of weeds, being found commonly in water bodies. The Roundup Original® is one of the most used glyphosate-based herbicides that presents in its basic composition isopropylamin glyphosate salt and a surfactant. Many studies suggest that the surfactant is the most lethal compound of Roundup s formulation. Among the Roundup® formulations, Roundup Transorb R® is the most recent. The main goal of this study was to evaluate the possible impacts of exposition to glyphosate (1 ppm), Roundup Original® (1ppm glyphosate acid equivalent e/a.) and Roundup Transorb R® (1ppm e/a) subletal concentrations on bullfrog tadpoles (Lithobates catesbeianus) activity level, cardiorespiratory and histological endpoints. The tadpole s activity level was significantly augmented only by the glyphosate exposition, suggesting that a stressful condition would divert energy from morphogenetic processes. All tested herbicides caused skin morphological alterations like cellular hypertrophy, hypertrophy of epithelium wall and chromatid rupture. The values in Control group were constant until the O2 tension of 40 mmHg suggesting that the critical O2 tension for this species is between 40 and 20mmHg. The exposure to glyphosate caused a significant reduction, possibly due to the observed epidermis hypertrophy, which reduces the O2 uptake. Roundup Transorb R® increased values, suggesting that the composition of inert compounds and surfactants in this formulation influences this parameter. There was no difference between the presented by the Roundup Original® and Control group, which suggests that the possible increase on O2 consumption caused by Roundup exposure was masque by the epidermis hypertrophy. The registered in loco cardiac frequency wasn t altered by the glyphosate and Roundup Original. Glyphosate caused a significant ventricular mass decrease. No difference was observed on Fc, TPT and THR of ventricular strips at sub-physiological stimulation frequencies (0,2 Hz). The Roundup Original® group was the only that presented changes induced by increases in the stimulation frequency, showing Fc increases and THR decreases. It is suggested that this formulation induces the NO production, which promotes cardiac relaxation. However, these increases in Fc and THR acceleration were completely abolished by the addition of adrenaline, suggesting the existence of an antagonistic interaction between the Roundup Original® and adrenaline.